Pemanfaatan Lahan Bekas Pertambangan Emas Tanpa Izin (PETI) Di Desa Temenggung Kecamatan Limun Kabupaten Sarolangun - Diki Pernandes; M. Nazori; Ahmad Syukron Prasaja (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
The large number of ex-illegal gold mines in Setajo Raya Subdistrict which was caused by illegal mining activities made the former mining land abandoned by the miners and no longer used. The number of losses incurred from these PETI activities include: changes in the color of river water, damaged soil due to excavation, river pollution. Seeing the condition of the problems that exist in the District of Setajo Raya, a research was carried out on "Utilization of Ex- Mining Gold Without Permits in Sentajo Raya District". This study aims to identify the use of ex-gold mining land without a permit in Sentajo Raya Subdistrict to minimize the bad effects of the former PETI mining and reuse the land. To achieve the goal, there are 3 (three) research objectives, namely Identifying the distribution of ex-mining gold without a permit in Sentajo Raya District, Identifying the potential for exploitation of ex-gold mining without a permit in Sentajo Raya Subdistrict and developing a strategy to use land for ex-gold mining without a permit in Sentajo Raya District. . This study uses spatial analysis which is used to identify ex-mining land with field observation methods, qualitative and quantitative analysis is used to determine the use of ex-mining land with a questionnaire method of 99 respondents and SWOT analysis is used to determine the strategy of using ex-mining land. The distribution of former gold mining without a permit in Sentajo Raya District has 8 points, the number of distribution of former gold mining. Potential land use there are 4 types of land use that can be used as a strategy for exploiting ex-gold mining land, namely, as fish farming land, tourist attractions, reservoirs, and agriculture. permits in Sentajo Raya District are used for fish cultivation